Comparison of botanical characters and physiological characteristics among different flue-cured tobacco genotypes in seedling transplanting period - Wu Shengjiang; Dian Ruili; Wei Kesu; Li Delun; Han Zhikang; Lin Yechun; Pan Wenjie; Xie Yishu (浙江大学学报. 农业与生命科学版, 2014)
Guizhou is the second largest province for tobacco production and acts as a typical moderate-flavor tobacco planting area in China. According to the data from Guizhou Province Tobacco Monopoly Bureau (Company), the planting area of characteristic tobacco varieties bred in Guizhou such as “Nanjiang 3” “Bina 1”, etc. has increased significantly in these years, and accounted for more than 50% of the total tobacco growing area in Guizhou since 2012. Meanwhile, the well-cellar style transplanting technology invented in Guizhou has spread throughout our country, but there is a very common problem during the tobacco production that the transplanted seedlings showed a lower quality. Therefore, it is important and necessary to study the quality of different flue-cured tobacco genotypes, in order to cultivate high-quality seedlings and highlight the features of flue-cured tobacco varieties bred in Guizhou.In order to further improve the quality of seedling used for the well-cellar style transplanting in Guizhou, the biomass, root morphology, plastid pigments content, electrical conductivity, pH value and photosynthetic characteristics of different flue-cured tobacco genotypes (i. e., “K326”“Nanjiang 3”“Bina 1”“Guiyan 2” “Jiucaiping 2”) were studied in seedling transplanting period.The results showed that the botanical characters of different flue-cured tobacco genotypes in seedling transplanting period were significantly different.“K326” had the best aboveground biomass (0.110 9 gram per plant) while “Guiyan 2” had the lowest aboveground biomass (0.092 5 gram per plant). As for root, “Guiyan 2” and “Bina 1” had a better root morphology, and their root dry mass were 0.042 4 gram per plant and 0.040 3 gram per plant, respectively. For the total biomass, “K326” and “Bina 1” had the largest dry mass, and their values were 0.149 3 gram per plant and 0.135 4 gram per plant, respectively. Physiological analysis illustrated that the difference in plastid pigments content and pH value was relatively small among different flue-cured tobacco genotypes in seedling transplanting period, but the difference in electrical conductivity values and photosynthetic characteristics indexes was quite significant.“Bina 1” had the highest plastid pigments content, containing 2.019 mg/g chlorophyll and 0.538 mg/g carotenoid, followed by “K326”, while “Jiucaiping 2” had the lowest plastid pigments content, containing 1.542 mg/g chlorophyll and 0.435 mg/g carotenoid. The pH values of “K326” (6.63) and “Bina 1” (6.76) were in the middle, and “Jiucaiping 2” (6.88) and “Nanjiang 3” (6.83) had the largest pH value, while “Guiyan 2” (6.43) was the smallest. The electrical conductivity values of “K326” and “Bina 1” were the smallest, while “Guiyan 2” had the largest electrical conductivity value. The absolute conductivity values of “K326” and “Bina 1” were 9.85 μS/cm and 9.08 μS/cm, and relative conductivity values were 15.63% and 21.45%, respectively. The absolute conductivity and relative conductivity values of “Guiyan 2” were 13.28 μS/cm and 29.84%, respectively. As far as the photosynthetic indexes, “K326” had the best performance among all the tested genotypes, followed by “Bina 1” and “Jiucaiping 2”, while “Guiyan 2” and “Nanjiang 3” were relatively poor.In summary, “Bina 1” and “K326” had better botanical characters and physiological characteristics among the different flue-cured tobacco genotypes tested in this study, showing better photosynthetic performance, stronger resistance and self-protective ability. Therefore, “Bina 1” and “K326” can be used as the main flue-cured tobacco varieties in Guizhou in the future.